Review on Networking and Control Technologies of Space Satellite Network - Xinyue LIAO; Ran ZHANG; Zhengxuan HUANG; Jiang LIU; Qinqin TANG; Tao HUANG (天地一体化信息网络)
With the rapid advancement of aerospace technology and satellite internet, high-speed and high-bandwidth satellite communication systems have gradually become an essential component of the next-generation mobile communication infrastructure.The trend in the development of satellite internet has propelled the commercialization process of satellite networks, with low earth orbit satellites playing a significant role in constructing satellite internet.The efficient and reliable network management of large-scale low earth orbit satellite networks, along with the integration of space and ground routing, has gradually emerged as a cutting-edge issue in the development of integrated aerospace networks.In recent years, as satellite networks have expanded in scale, numerous network management methods have been proposed.Firstly, begined by examining the development status of large-scale satellite constellations both domestically and internationally, surveying the existing network architecture and protocol systems of various satellite networks.Subsequently, based on the current development status of large-scale satellite networks, the challenges and key technologies involved in satellite management were analyzed.Finally, built upon the network integration of space and ground, existing solutions were extensively researched and analyzed.